FILSAFAT KETUHANAN DALAM BHAGAVAD GITA - Putu Sri Marselinawati (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
In the Hindu literature the Bhagavad Gita is one of the books that discusses the conception of God, which is in harmony with the philosophy of the Process or Philosophy of the Organizations of A.N.Whitehead. Etymologically, Bhagavad Gita is said to come from the words Bhagavad and Gita, Bhagavad means God and Gita means singing, So Bhagavad Gita is the song of God. In the discussion of God according to the Philosophy of Organisms or Process Philosophy, it will explain 4 processes, first God and creativity which means God as creator, this is mentioned in the Bhagavad Gita,